70 Availability of Personal Protective Equipment in NHS Hospitals During COVID-19: A National Survey. (12th October 2021) - Mantelakis, A; Spiers, H; Lee, C W; Chambers, A; Joshi, A
Abstract: Introduction: The continuous supply of personal protective equipment (PPE) in the National Health Service (NHS) is paramount in order to sustain a safe level of staffing and to reduce transmission of COVID-19 to patients, public and staff. Method: A 16-question survey was created to assess the availability and personal thoughts of healthcare professionals regarding PPE supply in England. The survey was distributed via social media (Facebook © and Twitter ©) to all UK COVID-19 healthcare professional groups, with responses collected over 3 weeks in March 2020 during the beginning of the pandemic. Results: A total of 121 responses from physicians in 35 different hospitals were collected (105 inpatient wards, 16 from intensive care units). In inpatient wards, eye and face protection were unavailable to 19.1% of respondents. Masks were available to 97.7% of respondents and gloves in all respondents (100%). Body protection was available primarily as a plastic apron (83.8%). All of respondents working in intensive care had access to full-body PPE, except FFP3 respirator masks (available in 87.5%). PPE is 'Always' available for 29.8% of all respondents, and 'Never' or 'Almost Never' in 11.6%. There was a statistically significant difference between London and non-London responders that 'Always' had PPE available (43.9% versus 19.0%, p = 0.003). Conclusions: This is the first survey to evaluate PPE supply in England during the COVID-19 pandemic. Our survey demonstrated an overall lack of PPE volume supply in the UK, with preferential distribution in London. Eye and full body protection are in most lack of supply.